1999
DOI: 10.1073/pnas.96.17.9845
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a temperate bacteriophage encoding the type III effector protein SopE from an epidemic Salmonella typhimurium strain

Abstract: Salmonella typhimurium employs the specialized type III secretion system encoded in pathogenicity island 1 (SPI1) to translocate effector proteins into host cells and to modulate host cell signal transduction. The SPI1 type III system and the effector proteins are conserved among all salmonellae and are thought to be acquired by horizontal gene transfer. The genetic mechanisms mediating this horizontal transfer are unknown. Here, we describe that SopE, a SPI1-dependent translocated effector protein, is present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
220
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(228 citation statements)
references
References 46 publications
5
220
0
3
Order By: Relevance
“…In addition, SPI-7 has a viaB operon which encodes the gene responsible for the synthesis and transport of the virulence antigen Vi (28,29). Studies have shown that Vi antigen may be important in the survival of the bacterium within macrophages though this may not be in cellular invasion of the macrophage or the intestinal wall (14,30).…”
Section: Molecular and Biologic Features Of Salmonella Typhimentioning
confidence: 99%
“…In addition, SPI-7 has a viaB operon which encodes the gene responsible for the synthesis and transport of the virulence antigen Vi (28,29). Studies have shown that Vi antigen may be important in the survival of the bacterium within macrophages though this may not be in cellular invasion of the macrophage or the intestinal wall (14,30).…”
Section: Molecular and Biologic Features Of Salmonella Typhimentioning
confidence: 99%
“…Recent studies have shown that acquired PAI are major contributors to the virulence nature of many pathogenic bacteria [60,63], including Salmonella where they are referred to as Salmonella Pathogenicity Islands (SPI). These chromosomally encoded regions typically contain large clusters of virulence genes and have the potential to increase the virulence of a micro-organism or even to transform a benign organism into a pathogen [100]. Until now, 12 SPI have been described.…”
Section: Source Of Emergence: Microbial Genome Evolutionmentioning
confidence: 99%
“…83 The P2-related Salmonella phage sopEf encodes, at this same location, the type III effector SopE, a virulence factor injected into eukaryotic cells via the Salmonella enterica type III secretion system. 84 Orf30 lies between genes S and V. It is nonessential, and transcribed constitutively from its own promoter at a low level. 49 Homologues of the predicted orf30 gene product are found in many E. coli genomes, but its function remains unknown.…”
Section: Accessory Genes ("Morons")mentioning
confidence: 99%